Experiential Marketing Strategy in International Marathon Running Event: A Qualitative Analysis of Generation Z Participants - Riu, Isma Azis (Malaqbi Publisher, 2025)
This qualitative study examines Generation Z’s engagement with experiential marketing strategies in international marathon events, focusing on the dynamic interplay between digital innovation, cultural authenticity, and emotional loyalty. Through a phenomenological analysis of 25 Gen Z participants (aged 18–26) at the Makassar International Marathon (2023–2024), the research identifies three core findings: (1) Gen Z’s preference for immersive, augmented reality (AR)-enabled pre-race activations over traditional sponsorships; (2) the pivotal role of social media as a platform for co-creating event narratives and fostering digital collectivism; and (3) the emergence of experience-driven loyalty, where cultural authenticity and memorable interactions supersede transactional rewards. The study reveals that Gen Z’s loyalty is contingent on glocalized strategies that harmonize global event standards with Makassar’s maritime heritage and youth-driven digital culture. Event organizers are urged to adopt hybrid experiential frameworks that balance technological advancements with grassroots human connections, shifting from service-dominant to experience-dominant marketing paradigms. These insights offer actionable pathways for enhancing participant engagement and positioning emerging destinations like Makassar as culturally resonant nodes in the global sports tourism landscape.